White Matter Microstructural Compromise Is Associated With Cognition But Not Posttraumatic Stress Disorder Symptoms in Military Veterans With Traumatic Brain Injury. Issue 5 (September 2016) - Sorg, Scott F.; Schiehser, Dawn M.; Bondi, Mark W.; Luc, Norman; Clark, Alexandra L.; Jacobson, Mark W.; Frank, Lawrence R.; Delano-Wood, Lisa
Abstract : Objective: To investigate white matter microstructure compromise in Veterans with a history of traumatic brain injury (TBI) and its possible contribution to posttraumatic stress disorder (PTSD) symptomatology and neuropsychological functioning via diffusion tensor imaging. Participants and Methods: Thirty-eight Veterans with mild ( n = 33) and moderate ( n = 5) TBI and 17 military control participants without TBI completed neuropsychological testing and psychiatric screening and underwent magnetic resonance imaging an average of 4 years following their TBI event(s). Fractional anisotropy (FA) and diffusivity measures were extracted from 9 white matter tracts. Results: Compared with military control participants, TBI participants reported higher levels of PTSD symptoms and performed worse on measures of memory and psychomotor-processing speed. Traumatic brain injury was associated with lower FA in the genu of the corpus callosum and left cingulum bundle. Fractional anisotropy negatively correlated with processing speed and/or executive functions in 7 of the 8 tracts. Regional FA did not correlate with memory or PTSD symptom ratings. Conclusion: Results suggest that current PTSD symptoms are independent of TBI-related white matter alterations, as measured by diffusion tensor imaging. In addition, white matter microstructural compromise may contribute to reduced processing speed in our sample of participants with history of neurotrauma. Findings of the current study add insight into the factors associated with complicated recovery from mild to moderate TBI.